An APEX2 proximity ligation method for mapping interactions with the nuclear lamina - Tran, Joseph R; Paulson, Danielle I; Moresco, James J; Adam, Stephen A; Yates, John R; Goldman, Robert D; Zheng, Yixian (The Journal of cell biology, 2021)
The nuclear lamina (NL) is a meshwork found beneath the inner nuclear membrane. The study of the NL is hindered by the insolubility of the meshwork and has driven the development of proximity ligation methods to identify the NL-associated/proximal proteins, RNA, and DNA. To simplify and improve temporal labeling, we fused APEX2 to the NL protein lamin-B1 to map proteins, RNA, and DNA. The identified NL-interacting/proximal RNAs show a long 3' UTR bias, a finding consistent with an observed bias toward longer 3' UTRs in genes deregulated in lamin-null cells. A C-rich motif was identified in these 3' UTR. Our APEX2-based proteomics identifies a C-rich motif binding regulatory protein that exhibits altered localization in lamin-null cells. Finally, we use APEX2 to map lamina-associated domains (LADs) during the cell cycle and uncover short, H3K27me3-rich variable LADs. Thus, the APEX2-based tools presented here permit identification of proteomes, transcriptomes, and genome elements associated with or proximal to the NL.